Effects of Acupressure on Pain in Chronic Diseases: A Scoping Review - Hatta, Candra; Handayani, Fitria; Erawati, Meira (GLOBAL HEALTH SCIENCE GROUP, 2024)
Pain is one of them sign the main thing felt by sufferers disease chronic , study handler non- pharmacological pain especially acupressure has Lots carried out, however, review studies are possible used as base thinking intervention This Still limited. Objective from this review is For see effect of acupressure against pain in disease chronic. This review use approach scoping review, with using Pubmed, ScienDirect, Proquest databases with using the keywords “ Acupressure” AND “Pain” AND “Cronic” OR “Cronic diases”. On search the done filtering data with initial filters checklist